Comportamiento agronómico y valoración nutricional de matarratón (Gliricidia sepium) y fleminga (Flemingia macrophylla). - Benites Alarcon, Verónica Matilde (2011)
In the property "The María" of the State Technical University of the canton Quevedo, county of The Ríos was determined the "agronomic Behavior and nutritional value of the Matarratón (Gliricidia sepium) and Flemingia (Flemingia macrophylla) in different states of maturity, where a design of complete blocks was used at random (DCA). The best indexes in the root weight (32,3 kg), weight of leaves (46,55 kg) and weight of shafts (21,2 kg) they register to the 80 days in the Matarratón, and to the 110 days the highest values are reported in forage weight (77,05 kg), relationship hoja:tallo (2,62) and relationship leaves aérea:parte radicular (9,35) with the same one leguminous. The biggest protein levels were also obtained with the leguminous Matarratón to the 80 and 140 days with the 19,74 and 21,98%. AND the lowest fiber levels are reported in the Flemingia to the 110 and 140 days with the 36,80 and 28,20%. For the composition microbiology, the tall populations in bacterias (5,9 x 10 5), actinomicetes (9,5 x 10 6), mushrooms (7,5 x 10 4), and fixers of N asymbiotic (3,9 x 10 3) to the 140 days they were presented with the Matarratón. The bigger than colonization percentage (90,24%) and endófitos density (5,59) it was also presented in the Flemingia to the 140 days.